1976
DOI: 10.3181/00379727-151-39304
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E Supplementation and Glutathione Peroxidase Activity

Abstract: Vitamin E and selenium have been recognized as physiological antioxidants in the prevention of oxidative damage to tissues. Rotruck et al. (1) found that selenium was able to help prevent oxidative damage to rat erythrocytes incubated with glucose, as evidenced by decreased hemolysis and decreased hemoglobin oxidation. Vitamin E , however, protected only against hemolysis, whether with or without glucose, but did not prevent hemoglobin oxidation. These results indicated that the effect of selenium was specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1977
1977
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Vitamin E deficiency induced a decrease in mitochondrial SOD in rabbit heart as measured by an indirect activity assay (19). Yang et al observed an inverse relationship between GPX activity and vitamin E staus in rat liver (20), as was found in the muscles in EXPT IL Such a change may be an adaptive response to the alteration in oxidant-antioxidant balance. Several previous observations have supported a close relationship between the glutathione redox system and vitamin E as cell defense mechanisms.…”
Section: Resultsmentioning
confidence: 73%
“…Vitamin E deficiency induced a decrease in mitochondrial SOD in rabbit heart as measured by an indirect activity assay (19). Yang et al observed an inverse relationship between GPX activity and vitamin E staus in rat liver (20), as was found in the muscles in EXPT IL Such a change may be an adaptive response to the alteration in oxidant-antioxidant balance. Several previous observations have supported a close relationship between the glutathione redox system and vitamin E as cell defense mechanisms.…”
Section: Resultsmentioning
confidence: 73%
“…Yang et al . [27] reported that both excess and deficient amounts of vitamin E significantly depress the activity of GSH-Px in liver and plasma of rats. Lin et al .…”
Section: Discussionmentioning
confidence: 99%
“…For example, Thomas and Stocker (2000) reported that vitamin E at high concentrations can serve as a prooxidant. In addition, Yang et al (1976) reported that both excess and deficiency of vitamin E in rats significantly depress the activity of glutathione peroxidase and thus modulates the intracellular glutathione pool. Thus, we speculated that excess dose of vitamin E could modify the overall balance of antioxidants in a cell, resulting in different pools of antioxidant compound that carry different immunoregulatory properties.…”
Section: Discussionmentioning
confidence: 99%